Mediatization of Everyday Life and Family Health - Mansoore Tabrizi (مطالعات رسانه‌های نوین, 2019)
Family is one of the most important social units and its health is very effective in the health of the community and its members. The mediatization of everyday life is a process that refers to the continuous bonding of the individual's everyday life to the media, a process that can affect the health of the family. Accordingly, in this research, focusing on 530 families with a child, using the survey method, the relationship between the mediatization of everyday life and family health (including five dimensions), and the effect of the consumption of each of the three media of the internal TV, Satellite programs and the Internet were questioned. The results of the research indicate that the mediatization of everyday life has a significant negative correlation with family health and this relationship is visible in the dimensions of family relational and process health. In a more detailed analysis, the two dimensions of mediatization of identity and the mediaization of interactions have had a negative correlation with the overall index of family health and family relational health. Internet usage and satellite usage have also decreased with the increase in media out of the family's health, and the use of internal television has not played a role in the media process.